ANALISIS KEBUTUHAN BEBAN PENDINGIN DENGAN METODE COOLING LOAD TEMPERATURE DIFFERENCE (CLTD) PADA RUANG LOBBY GEDUNG SIMULATOR SEKOLAH TINGGI PENERBANGAN INDONESIA - Arief Susanto; Yenni Arnas; Zulham Hidayat (Politeknik Penerbangan Indonesia Curug, 2017)
Simulator Building is one of the buildings in Indonesia Civil Aviation Institute, which is used as supporting educational facilities. This simulator building has three floors and a lobby on the first floor which is used as the meeting room and reception area. On this building, there is already a centralized air conditioning type whose channels are distributed throughout the room in this building including a lobby room on the first floor. But, those air conditioning equipment is not working. Thus, it is causing the temperature in the lobby room calculated as 28°C - 30°C during the daylight. Those condition is exceeding the maximum thermal comfort threshold for tropics which is 22,8°C – 25,8°C. It is over the limit of maximum thermal comfort condition for the tropics, which is 22,8°C- 25,8°C. Therefore, it needs an air conditioner (AC) to keep the room temperature comfortable. in planning the installation of the eqquipment, we can analyze it by Cooling Load Temperature Difference (CLTD) calculation method for Indonesian comfort thermal zone which is generally 25oC ± 1oC on temperature and 55 % ± 10 % on relative air humidity